A chorus line [videorecording (Blu-Ray)] - Bennett, Michael, 1943-1987; Kirkwood, James, 1924-1989; Dante, Nicholas (20th Century Fox Home Entertainment [Distributor], 2013)
After narrowing down hundreds of Broadway hopefuls, Zach leads a select group of dancers on the tryout of their lives. In an audition twist, Zach asks each performer personal and intimate questions with results that powerfully affect not only the young performers, but the hardened stage veteran as well.